(untitled) (Medico Legal Update, 2021)
It is important for all pregnant women throughout their gestational period to be able to access information, services and care by having direct communication with their doctors or their healthcare provider or their relatives. With the proliferation of mobile devices and the internet it has become very easy to get access to such information in a quick and efficient manner. There are also several awareness programs which teach about the right kind of physical activity and food to be followed by such pregnant women. Having access to such information helps these women identify and prevent any pregnancy related complications or risks which could lead to issues such as still-birth, pre term labor etc. Women who do not use this information wisely are likely to be putting their lives as well as the lives of their babies at risk. The main objective of this paper is to analyse various compound reasons pregnancy related issues and the technologies available to solve such issues.